GPU-accelerated real-time motion planning for safe human-robot collaboration - Fujii, Shohei (Nanyang Technological University, 2024)
Robotic automation has a significant role in industry over decades. As the demand for complex tasks increases, there has been a recent anticipation for robotic automation in human-robot collaborative environments, leading to the introduction of commercial collaborative robots. However, current robot controllers reduce the speed of robots to secure the safety of humans, which results in conservative behavior and lower performance with collaborative robots. A challenge in this thesis is to maximize the productivity of collaborative robots while ensuring safety, aiming for productivity of robots under collaborative situations comparable to that of traditional robots.